The Influence of Digital Leadership and Organizational Culture on Millennial Employee Creativity at the West Sulawesi Communication, Informatics, and Coding Agency - Nurazila, Nurazila; Muh. Rezky Naim; Suharlina (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
In the digital age, technological literacy is an important factor in supporting community participation in various aspects of life, including the economy, education, and public services. However, the level of technological literacy in Indonesia, especially in areas such as West Sulawesi, is still relatively low. This can be seen from the limited understanding of the community in using technology effectively and safely, as well as the low utilization of digital services provided by the government. As the agency responsible for communication and information technology, the West Sulawesi Communication and Information Agency is expected to play an active role in improving the technological literacy of the community This study aims to determine the effect of Digital Leadership and Organizational Culture on Millennial Employee Creativity at the West Sulawesi Communication, Informatics, and Encryption Agency. The research method used was a survey with a saturated sampling technique, in which all subordinate employees who met the research criteria were included in the sample. The sample size was 64 millennial employees. The results of the study indicate that Digital Leadership does not influence Millennial Employee Creativity, with a significance value of 0.00>0.05. Organizational Culture has a significant partial effect on Millennial Employee Creativity with a significance value of 0.00<0.05. Organizational Culture has a strong and significant effect on Millennial Employee Creativity, while Digital Leadership does not have a significant effect on Millennial Employee Creativity in this model.